Potencialidades e limites no atendimento a pessoas em situação de violência doméstica: a experiência do Município de Suzano - Damasceno, Magna Barboza (2017)
The present research proposed to hold a debate about domestic violence based on the experience lived in the Municipal Health Department of the city of Suzano. For this, the historicity of the organization of the Network of Attention to People in Situation of Domestic and / or Sexual Violence, was recovered from the place of management occupied by the researcher, with the objective of analyzing the potentialities and limits of the care provided by professionals To cases of domestic violence. We used as a reference the cartographic method, which allowed us to develop the path in which professionals establish connections in the formation of microreds, as well as identifying the conceptions that they have of violence as a work object. In this social cartography through historical documents, semi-structured interviews, online questionnaire and epidemiological data, forms of narratives were developed that showed in the entangled existential field the crossings and transversalities embedded in the everyday of knowing how to do health, the fragilities contained in the political context of management, and The care practices performed by health professionals, as well as the points that signal power in the construction of the policy to combat domestic violence. We find as a result the organization in network, the bond or bond as a tool of high power, founding aspects that expands social technology in front of the problematic and propitiate transformation. We also find feelings of loneliness, recrudescence, that make it impossible to build micro political networks through conceptions that challenge the creative and paralyzing bias. It was also possible to find out how the network of care was designed for people in situations of domestic and / or sexual violence and the paths traveled by professionals